2019
DOI: 10.1590/1678-4324-2019180083
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Immune Response of Pangasius hypophthalmus Fed Diets Containing Seaweed Extracts as Immunostimulant

Abstract: Growth and immune response of Pangasius hypophthalmus were evaluated after feeding the fish with diets containing hot-water extracts (HWE) of Sargassum oligocystum as immunostimulant at 100, 300, and 500 mg kg-1 diet. Basal diet for P. hypophthalmus served as the control. The experimental diets were administered for 12 weeks. At the end of the feeding experiment, growth and haematological profile of fish were evaluated. Result showed that final weight, weight gain, daily growth rate and feed conversion ratio w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Effects of seaweed supplementation on blood cell counts are variable; studies in human or other mammals showed limited effects [ 6 , 8 ], but increased counts were observed when chicken and fish were fed Laminaria japonica or Sargassum oligocystum , respectively [ 9 , 10 ]. Such addition to animal feed is not only associated with increased growth and feed conversion ratios in chicken and fish, but also enhanced status of innate and adaptive immune defenses and immune responsiveness and survival after infectious challenge [ 11 , 12 , 13 ].…”
Section: Whole Seaweed or Crude Extract Supplementationmentioning
confidence: 99%
“…Effects of seaweed supplementation on blood cell counts are variable; studies in human or other mammals showed limited effects [ 6 , 8 ], but increased counts were observed when chicken and fish were fed Laminaria japonica or Sargassum oligocystum , respectively [ 9 , 10 ]. Such addition to animal feed is not only associated with increased growth and feed conversion ratios in chicken and fish, but also enhanced status of innate and adaptive immune defenses and immune responsiveness and survival after infectious challenge [ 11 , 12 , 13 ].…”
Section: Whole Seaweed or Crude Extract Supplementationmentioning
confidence: 99%
“…There are no other studies addressing this topic in fish, but dietary supplementation with aquatic plants, which are abundant in phytol, improved fish growth performance. For example, dietary fortification with common duckweed, Lemna minor meal [26], Sargassum oligocystum hot-water extract [27], and Entromorpha intestinalis extract [28] significantly improved the growth performance of rohu, Labeo rohita, Iridescent shark, Pangasius hypophthalmus, and electric yellow cichlid, Labidochromis caeruleus, respectively.…”
Section: Discussionmentioning
confidence: 99%